Error Reduction, Convergence and Optimality for Adaptive Mixed Finite Element Methods for Diffusion Equations (Journal of Computational Mathematics, 2018)
Error reduction, convergence and optimality are analyzed for adaptive mixed finite element methods (AMFEM) for diffusion equations without marking the oscillation of data. Firstly, the quasi-error, i.e. the sum of the stress variable error and the scaled error estimator, is shown to reduce with a fixed factor between two successive adaptive loops, up to an oscillation. Secondly, the convergence of AMFEM is obtained with respect to the quasi-error plus the divergence of the flux error. Finally, the quasi-optimal convergence rate is established for the total error, i.e. the stress variable error plus the data oscillation.
Keywords: Adaptive mixed finite element method; Error reduction; Convergence; Quasi-optimal convergence rate.